MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA KOMUNIKASI PERSUASIF DALAM VIDEO ENDORSEMENT PRODUK KULINER PADA AKUN SELEBGRAM HINDU @jejakimade - Pratyaksa, I Gede Titah; Eka Putri, Ni Luh Wiwik (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
The phenomenon of product endorsements by Hindu celebrities is increasingly common on Instagram social media. One of them is the @jejakimade account, which is one of the popular public figures on the platform who often shares endorsements on Instagram social media. Persuasive communication carried out by @jejakimade is very important in influencing the audience. The theory used includes cognitive dissonance theory. The results of the study show that marketing communication carried out on the @jejakimade account in product endorsement videos on Instagram social media using @jejakimade tries to overcome the doubts of potential consumers by presenting more comprehensive information. The information conveyed by @jejakimade has the potential to change or strengthen the beliefs of potential consumers towards the products they want to buy. In conveying the message, @jejakimade provides information in the form of insight into culinary products to its followers.